An Empirical Analysis of Crime in Jamaica - Horatio Morgan, Nicole Samuels (My University, 2016)
Previous studies have found that changes in crime can be significantly explained by disparities and changes in income as well as educational availability and investment in social programs. Guided by the results of these studies as well as Merton Strain theory and Becker’s economic theory of crime, this study investigates the relationship between crime and income, labour participation, education, public social investment and also elections. The OLS estimates of the linearly detrended model of crime revealed that labour participation, education and public social investment significantly influenced crime in Jamaica.